Characterization and modelling of naturally fractured granites in the Redang Island, Terengganu, Malaysia - Askury Abd Kadir, Mohd Razlan Abdul Rahman, Choong Chee Meng, Fa, . (2015)
The Redang Island is situated in the east coast of Peninsular Malaysia, in the state of Terengganu. Geologically, it is mainly composed of medium-to coarse-grained biotite- hornblend granite and overlain by sedimentary and metamorphic rocks. The close-spaced fractured pattern gave an indicator for the active tectonic, which create a fractured basement in Anding Utara that situated 200km SE of the study area.